2008
DOI: 10.1176/ps.2008.59.12.1430
|View full text |Cite
|
Sign up to set email alerts
|

New Endeavors, Risk Taking, and Personal Growth in the Recovery Process: Findings From the STARS Study

Abstract: Enduring, strong, collaborative relationships provide a healthy framework for discussions between patients and clinicians about taking on new activities, roles, or responsibilities and increase the likelihood that new activities and opportunities will be planned and carried out in ways that promote, rather than endanger, recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 32 publications
(11 reference statements)
0
14
0
Order By: Relevance
“…Direct involvement of people in their own risk assessments may lead to more well-informed assessments and open up the possibility of focusing on micro-level relationships (individuals, family, household, community) that enable people to benefit from supports that in themselves can successfully manage or reduce risk behaviours and aid recovery. 64,65 Care coordinators could engage in conversations about risk with people they work with allowing service user and professional accounts to stand side by side as credible versions of the day-to-day realities of living with mental distress. This will not only allow service users to benefit from the expert opinion of care coordinators, but help workers to see the broader range of risk concerns that people encounter in their everyday lives.…”
Section: Ordinary Risks and Accepted Fictionsmentioning
confidence: 99%
“…Direct involvement of people in their own risk assessments may lead to more well-informed assessments and open up the possibility of focusing on micro-level relationships (individuals, family, household, community) that enable people to benefit from supports that in themselves can successfully manage or reduce risk behaviours and aid recovery. 64,65 Care coordinators could engage in conversations about risk with people they work with allowing service user and professional accounts to stand side by side as credible versions of the day-to-day realities of living with mental distress. This will not only allow service users to benefit from the expert opinion of care coordinators, but help workers to see the broader range of risk concerns that people encounter in their everyday lives.…”
Section: Ordinary Risks and Accepted Fictionsmentioning
confidence: 99%
“…Prior qualitative studies suggested that clients with serious mental illness are more likely to be in recovery when they develop consistent relationships with treatment providers who support a Bnormal^rather than Bmentally ill^identity. 21 Collaborative relationships between clients and treatment providers include a balance of support and encouragement without excessive pressure placed on clients to meet treatment provider expectations, 22,23 and treatment providers with successful outcomes place a strong emphasis on a partnership-oriented relationship between treatment provider and client. 24 Clients with serious mental illness identify the following priorities for effective therapeutic relationships: sharing common ground, feeling known, the importance of talk, practitioner availability and flexibility, and opportunities for input into treatment planning and choices regarding treatment modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Receiving the instructors trust can be interpreted as a way of supporting vulnerable citizens to take on new roles and responsibility (Davidson & Chan, 2014; Deegan, 1996; Young, Green, & Estroff, 2008) and the feeling of mutual trust may also be interpreted as an explanation for why the participants appreciated the instructors’ ability to personally challenge them during their participation in the intervention.…”
Section: Discussionmentioning
confidence: 99%